In Situ Determination Of Layer Thickness And Elastic Moduli Of Asphalt Pavement Systems By Spectral Analysis Of Surface Waves (Sasw) Method - Sri Atmaja P Rosyidi; Mohd Azmi Ismail; Abdul Rahim Samsudin; Mohd Raihan Taha; Abdul Ghani Rafek; Khairul Anuar Mohd Nayan (Universitas Muhammadiyah Yogyakarta, 2005)
Spectral analysis of surface waves (SASW) is a non-destructive and in situ method for determining the stiffness profile of soil and pavement sites. The method consists of generation, measurement, and processing of dispersive elastic waves in layered systems. The test is performed on the pavement surface at strain level below 0.001%, where the elastic properties are considered independent of strain amplitude. During an SASW test, the surface of the medium under investigation is subject to an impact to generate energy at various frequencies. Two vertical acceleration transducers are set up near the impact source to detect the energy transmitted through the testing media. By recording signals in digitised form using a data acquisition system and processing them, surface wave velocities can be determined by constructing a dispersion curve. Through forward modeling, the shear wave velocities can be obtained, which can be related to the variation of stiffness with depth. This paper presents the results of two case studies for near-surface profiling of two different asphalt pavement sites.